ADHD_Wiki_Collaborate Programme: Fostering ADHD Students’ Cooperative and Social Skills Using Web 2.0 Tools - Eleni Moudatsaki; Inmaculada Marín-López; Rocío Luque-González (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
The characteristics of Attention Deficit Hyperactivity Disorder (ADHD) have an impact on collaborative and social skills. Web 2.0 tools, when used in psychoeducational activities, contribute to these skills’ improvement. This study aims to explore the effectiveness of an intervention programme by using a wiki tool to improve cooperation and socialization skills among peers in class groups where there is at least one student with ADHD. A single-group wiki-based intervention programme was designed and implemented over 15 weeks. Participants were 191 students from a secondary school in Greece, aged 12 and 13 years old. The results showed that ADHD students’ preference to group work was enhanced, while their preference to individual work as well as their difficulty of adjustment to group work decreased. Moreover, their cooperative skills and empathy improved, whereas irritability and disturbance decreased. ADHD students with social and cooperative skills’ deficits could be benefited from this intervention.